Dynamically directing cell organization via micro-hump structure patterned cell-adhered interfaces. Issue 14 (16th June 2020) - Yang, Wenguang; Sun, Lujing; Cai, Shuxiang; Chen, Yibao; Liang, Wenfeng; Zhou, Peilin; Yu, Haibo; Wang, Yuechao; Liu, Lianqing
Abstract : We present a simple method to fabricate micro-hump patterned interfaces based on electrohydrodynamic jet (E-jet) printing to control and direct cell organization. Microstructures were rapidly fabricated and cell adhesion was significantly enhanced by the micro-hump structures. Abstract : Cell adhesion plays an important role in cell communication, organ formation and tissue maintenance. Spatial microstructure patterning has the capability to regulate cell functions such as cell adhesion and cell proliferation as well as cellular mechanical properties. In this study, we present a simple method to fabricate micro-hump patterned interfaces based on electrohydrodynamic jet (E-jet) printing to control and direct cell organization. Micro-hump structures were rapidly fabricated by E-jet printing and arbitrary cell patterns can be achieved by selective cell adhesion induced by this surface topography. Furthermore, cellular mechanical properties were regulated by changing the density of microstructures. The technique we proposed could dynamically direct cell organization in a controlled manner, providing help for exploring the fundamental mechanism of cell adhesion and sensing.